Características agronómicas del pasto quiebra barriga (Trichanthera gigantea) en la estación experimental “El Padmi” de la Universidad Nacional de Loja - Casanova Erique, Santiago Fernando (2023)
The present investigation was carried out with the purpose of evaluating the agronomic characteristics of Quiebra Barriga (Trichanthera gigantea) in the Experimental Station "El Padmi" of the National University of Loja. For this purpose, in a culture of (Trichanthera gigantea) previously established, the culture and equalization cut were carried out and we proceeded to collect and record data on the variables under study at 60, 120 and 180 days. The following variables were evaluated: plant height, number of leaves, number of stems, leaf weight, stem weight, leaf/stem ratio, green forage production, dry matter content, and dry matter production. Data were processed and subjected to an analysis of variance using a completely randomized design (DCA) and Tukey's test (P <0.05) of significance. The results showed a statistical difference (P<0.0001) between the cutting ages for all the variables, with values greater than 180 days of cutting, obtaining this age a height of 1.26 meters; 138 leaves/plant, 17 stems/plant, 408 g of leaves, 382 g of stems and 1.1 RHT, 47.42 t/ha/cut of green forage, 12.85 t/ha/cut of dry forage and 27% dry matter. It is concluded that Trichanthera gigantea reaches its maturity after 120 days, since there is a balance in the productive and nutritional part, and it also adapts very well to the edaphoclimatic conditions of the region. It is recommended to implement the cultivation of Trichanthera gigantea as a fodder bank to complement the feeding of cattle in the warm tropics. Key words: Trichanthera gigantea, growth, cutting age, forage production, humid warm tropics